THE INFLUENCE OF WORK POLICIES AND WORK CONFLICT ON EMPLOYEE INTENTION - Ahdiyat Agus Susila (Faculty of Islamic Economics and Business, 2021)
This study aims to determine the effect Worklife-Policies, Work Involvement, and Work-Family Conflict on Turnover Intention of employees at PT.Sinar Bodhi Cipta, Tanjungpinang. This type of research uses a quantitative descriptive method. The sample in this study consisted of 93 people, namely employees of PT. The sample technique used in this study was the distribution of proportion sampling. The data analysis method used consisted of testing the quality of the data (validity). and reliability) Test classic assumptions (normality, heteroscedasticity, multicolonierity, and autocorrelation) Hypothesis test (t test and f test), multiple linear regression test and coefficient of determination. Data analysis using SPSS 21 multiple linear regression. The results of this study obtained the equation multiple linear regression Y = 0.8499 + 0.326X1 + (-0.197X2) + 0.786X3 + e and R2 = 0.731 or 73.1%. The t test results for the work-life policies (X1) variable on turnover intention Y obtained tcount 3.186>ttable 1.987 and a sig of 0.002 <0.05. In the variable Job Involvement (X2) on turnover intention Y obtained tcount-3,262>ttable 1.987 and sig 0.002 <0.05, and Workfamily Conflict (X2) on turnover intention Y obtained tcount 7.437> 1.987 and a sig of 0.000 <0.05. Based on the results obtained, it can be concluded that the work-life policies, Job Involvement, and Workfamily Conflict variables partially or simultaneously have a positive and significant effect on employee turnover intention at PT Sinar Bodhi Cipta, Tanjungpinang with a contribution of R square of 73.1%. In the variable Job Involvement (X2) on turnover intention Y obtained tcount-3,262>ttable 1.987 and sig 0.002 <0.05, and Workfamily Conflict (X2) on turnover intention Y obtained tcount 7.437> 1.987 and a sig of 0.000 <0.05. Based on the results obtained, it can be concluded that the work-life policies, Job Involvement, and Workfamily Conflict variables partially or simultaneously have a positive and significant effect on employee turnover intention at PT Sinar Bodhi Cipta, Tanjungpinang with a contribution of R square of 73.1%. In the variable Job Involvement (X2) on turnover intention Y obtained tcount-3,262>ttable 1.987 and sig 0.002 <0.05, and Workfamily Conflict (X2) on turnover intention Y obtained tcount 7.437> 1.987 and a sig of 0.000 <0.05. Based on the results obtained, it can be concluded that the work-life policies, Job Involvement, and Workfamily Conflict variables partially or simultaneously have a positive and significant effect on employee turnover intention at PT Sinar Bodhi Cipta, Tanjungpinang with a contribution of R square of 73.1%.